Changing perceptions of meritocracy in senior women's careers - Sealy, Ruth (Emerald, 2010)
Purpose – The aim of this paper is to explore how an elite group of senior women in banking represent and describe their understanding and experience of the role of meritocracy, within the context of their own career. Design/methodology/approach – Semi-structured interviews were conducted with 33 senior female directors from six global investment banks. Template analysis was used in the qualitative analysis of the coding. Findings – The paper found that the women's adherence to the notion of meritocracy diminished over time, as merit appeared to be less defined by human capital (ability and experience) and more by social capital (seen as political behaviour). The paper also reveals how the concept is construed on two levels: first, on a symbolic level, demonstrating how the organization defines and rewards success; second, on a personal level, how it affects the individual's cognitions, emotions and self-belief. Originality/value – This paper contributes to the small literature on the concept of meritocracy in the management field, with an emphasis on the experiences of successful female directors in global investment banks.
Keywords: Women directors; Glass ceilings; Career development; Banking